The Problem of Drug Interactions Between Rosuvastatin and Ticagrelor in the Aspect of the Risk of Rhabdomyolysis: Discussion of the Problem and Description of the Clinical Case - O. V. Gaisenok; Yu. M. Chichkov; M. V. Leonova (Столичная издательская компания, 2022)
Background. Combination therapy with two antiplatelet agents (ticagrelor or clopidogrel plus acetylsalicylic acid) and a high dose statin is recommended in accordance with clinical guidelines for patients undergoing acute coronary syndrome and coronary intervention. Combined therapeutic regimens have drug-drug interaction potential. Rhabdomyolysis is a known side effect of statin therapy, and there is evidence that co-therapy with ticagrelor increases the risk of this complication.Case description. A 72-year-old female patient was hospitalized with typical signs of rhabdomyolysis: muscle pain, oliguria, weakness, significant increases in creatine kinase (CK), myoglobin and creatinine. One month before that, she was urgently hospitalized with acute recurrent ST-elevation myocardial infarction and underwent endovascular intervention on a critical stenosis of the left anterior descending artery with stent implantation. After that, rosuvastatin 40 mg per day and ticagrelor 90mg 2 times a day were added to her therapy. During the current hospitalization, rosuvastatin, ACE inhibitors and spirolactone were canceled, infusion therapy was carried out, which led to a rapid regression of symptoms, restoration of adequate diuresis, and normalization of CK, myoglobin and creatinine levels. Conclusions. The combined use of ticagrelor with rosuvastatin (especially at a high dose) increases the risk of rhabdomyolysis in elderly patients. Patients taking ticagrelor may require changes in statin therapy, dose adjustments, and possible drug changes to avoid pharmacological interactions and an increased risk of side effects.